Sistem Kontrol Peralatan Listrik Jarak Jauh Berbasis Arduino - Nauval Pramana Putra; Irma Husnaini (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
The need for electrical energy is vital because electrical equipment generally uses electricity as the main energy. Electricity is energy that comes from petroleum which must be saved in its use. To save electricity usage, it is necessary to use electricity as efficiently as possible by not allowing this energy to be wasted. This paper aims to design an application for controlling electrical equipment remotely using the internet network. This tool uses Esp8266 as a link with the internet network, and uses applications on Android as a controlling media. When esp8266 is connected to the internet network and the on / off button on the android application is pressed, the ac and fan lights will turn on or off according to the button pressed. The results of testing this remote electrical appliance controller are that the tool can work properly turning on or off the lights and fans when connected to the internet without distance restrictions.